Assessment of Knowledge, Attitude and Practice of University Students towards Sustainable Development Goals (SDGs) - Nusrat Afroz; Zul Ilham (Pusbindiklatren Bappenas, 2020)
This study was performed to determine the awareness level of University of Malaya students towards Sustainable Development Goals (SDGs). A set of survey questionnaires based on knowledge, attitude, and practice (KAP) was distributed among all the students of University of Malaya and 382 responses were obtained to analyze the awareness level (95% confidence level with ±5% margin of error). Data analysis was performed SPSS Statistics version 20. Descriptive statistics showed that the respondents have high knowledge with a positive attitude towards SDGs. Spearman’s rho coefficient correlation was applied to determine the relationships between variables (knowledge with practice and attitude with practice). The results revealed a weak negative correlation between the knowledge and practice towards SDGs (r = -.264, N = 382, p = .00). However, there is a strong positive correlation between the attitude and practice towards SDGs (r = .440, n = 382, p =. 00).